A Specialized Histone H1 Variant Is Required for Adaptive Responses to Complex Abiotic Stress and Related DNA Methylation in Arabidopsis . Issue 3 (8th September 2015) - Rutowicz, Kinga; Puzio, Marcin; Halibart-Puzio, Joanna; Lirski, Maciej; Kotliński, Maciej; Kroteń, Magdalena A.; Knizewski, Lukasz; Lange, Bartosz; Muszewska, Anna; Śniegowska-Świerk, Katarzyna; Kościelniak, Janusz; Iwanicka-Nowicka, Roksana; et al.
Abstract : Stress-inducible linker histone variant is required for adaptive response of Arabidopsis to complex environmental stress. Abstract: Linker (H1) histones play critical roles in chromatin compaction in higher eukaryotes. They are also the most variable of the histones, with numerous nonallelic variants cooccurring in the same cell. Plants contain a distinct subclass of minor H1 variants that are induced by drought and abscisic acid and have been implicated in mediating adaptive responses to stress. However, how these variants facilitate adaptation remains poorly understood. Here, we show that the single Arabidopsis ( Arabidopsis thaliana ) stress-inducible variant H1.3 occurs in plants in two separate and most likely autonomous pools: a constitutive guard cell-specific pool and a facultative environmentally controlled pool localized in other tissues. Physiological and transcriptomic analyses of h1.3 null mutants demonstrate that H1.3 is required for both proper stomatal functioning under normal growth conditions and adaptive developmental responses to combined light and water deficiency. Using fluorescence recovery after photobleaching analysis, we show that H1.3 has superfast chromatin dynamics, and in contrast to the main Arabidopsis H1 variants H1.1 and H1.2, it has no stable bound fraction. The results of global occupancy studies demonstrate that, while H1.3 has the same overall binding properties as the main H1 variants, including predominant heterochromatin localization, it differs from them in its preferences for chromatin regions with epigenetic signatures of active and repressed transcription. We also show that H1.3 is required for a substantial part of DNA methylation associated with environmental stress, suggesting that the likely mechanism underlying H1.3 function may be the facilitation of chromatin accessibility by direct competition with the main H1 variants.